2010
DOI: 10.1111/j.1469-185x.2010.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic patterns in the distribution of social systems in terrestrial arthropods

Abstract: The role of ecology in the evolution and maintenance of arthropod sociality has received increasing research attention in recent years. In some organisms, such as halictine bees, polistine wasps, and social spiders, researchers are investigating the environmental factors that may contribute to high levels of variation in the degree of sociality exhibited both among and within species. Within lineages that include only eusocial members, such as ants and termites, studies focus more on identifying extrinsic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 141 publications
(215 reference statements)
2
78
0
Order By: Relevance
“…Similarly, in ants, species in 17 of 19 genera and five of six subfamilies tend to have larger colony sizes at high latitudes [2] (cf. [4]). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in ants, species in 17 of 19 genera and five of six subfamilies tend to have larger colony sizes at high latitudes [2] (cf. [4]). …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on testing four key hypotheses of cooperative breeding theory (Table 1) using broad comparisons of relevant ecological, social and life history variables across multiple species of birds, mammals and insects (Cockburn, 1996;Arnold and Owens, 1998;Johnson et al, 2002;Purcell, 2011). Essentially, these studies have investigated the evolution of sociality by phylogenetic comparative analysis, comparing differences in key variables between multiple social and asocial species within a given lineage.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…Comparative analyses are ideal for the study of large scale environmental influences on the evolution of sociality since their very aim is to compare patterns across multiple taxa or within a single species over large geographic areas. Such analyses have demonstrated that there is a non-random geographic distribution of sociality in a variety of taxa (Jetz and Rubenstein, 2011;Purcell, 2011). For example, Purcell (2011) conducted an extensive review of the literature pertaining to arthropod sociality along latitudinal and altitudinal gradients, and reanalyzed five previous case studies of social spiders and four ant subfamilies.…”
Section: Ecological Factorsmentioning
confidence: 99%
See 2 more Smart Citations